Observations of High Densities at Low Altitudes in the Nightside Ionosphere of Mars by the MAVEN Radio Occultation Science Experiment (ROSE). Issue 11 (10th November 2022) - Withers, P.; Felici, M.; Mendillo, M.; Vogt, M. F.; Barbinis, E.; Kahan, D.; Oudrhiri, K.; Gray, C.; Lee, C. O.; Xu, S.; Lester, M.; Sanchez‐Cano, B.; et al.
Abstract: Unusually large peak electron density values of ∼5 × 10 10  m −3 are sporadically observed in the nightside ionosphere of Mars in regions of strong and open crustal magnetic field. However, the associated vertical structure of the ionosphere has not previously been observed. Here, we present three vertical electron density profiles from the nightside ionosphere of Mars that have comparably large values of peak electron density. They were acquired by the Radio Occultation Science Experiment on the MAVEN spacecraft on 23, 24, and 29 March 2021. In these profiles, the peak density is large (2–4 × 10 10  m −3 ), the peak altitude is low (60–90 km), and the plasma layer is broad (full width at half maximum greater than 100 km, Chapman layer lengthscale of ∼30 km). Even if the peak altitude is at the upper end of this range, 90 km, the plasma density at 60 km would still be large, approximately 70% of the peak density. These findings hold even if the ionosphere was patchy, not spherically symmetric, during these observations. These three profiles were acquired at times when fluxes of energetic protons, but not electrons, were enhanced above background levels. The apparent association of large nightside electron density values with protons, rather than electrons, is contrary to previous findings. Key Points: Nightside ionospheric layers with peak density of 2–4 × 10 10  m −3, peak altitude of 60–90 km, and thicknesses >100 km are seen on Mars These layers are seen in association with enhanced fluxes of energetic protons, but not electrons These findings hold if the ionosphere is patchy, not spherically symmetric, over the observed region